Research on the Dynamic Characteristics of High-Speed Rotors Supported by a Double Layer Squeeze Film Damper-Bearing Composite Structure - Wei Wang; Weimin Wang; Weibo Li; Jiale Wang; Tianqing Li (IEEE Access)
In this study, a dynamic model for a damper-bearing-rotor system featuring a novel double layer squeeze film damper-bearing composite structure was developed, addressing the limitations of conventional single layer dampers in providing sufficient vibration damping for high-speed advanced mechanical equipment, such as aircraft and rocket engines. A 12-degree-of-freedom Timoshenko beam element was employed to construct a finite element model of a rotor system subjected to unbalanced and nonlinear oil film force excitation. An approach for decreasing the iterative dimension of high-dimensional local nonlinear systems has been devised, which considerably improves the efficiency of transient solutions for dynamic equations. The transient excitation process of an unbalanced rotor with multilayer oil film bearings was analyzed, and the Reynolds equations for the dampers and bearings were solved using the finite element method. The results indicate that the double layer squeeze oil film damper-bearing composite structure exhibited high stability, excellent impact resistance, and significantly reduced rotor amplitude at both high and critical speeds. Double layer squeeze film dampers provide a more evident vibration suppression benefit and can reduce vibrations more effectively at high speeds than single-layer squeeze film dampers. Within the range of 1‰ to 2‰ of the journal radius, increasing the radial clearance of the oil film bearings and double-layer squeeze film dampers can further reduce the rotor vibration amplitude under high-speed conditions. Additionally, experimental equipment was used to verify all three phenomena, and the results of the experiments demonstrated a high degree of agreement with the results of the numerical simulation.